2015
DOI: 10.1177/1526602815581597
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Comparative Outcomes of Carotid Artery Stenting Following Previous Carotid Endarterectomy vs De Novo Lesions

Abstract: Purpose: To report the long-term outcomes of patients who underwent carotid artery stenting (CAS) for de novo carotid stenosis vs patients treated for restenosis after carotid endarterectomy (CEA). Methods: A retrospective review was conducted of all 385 patients (mean age 68.6±9.6 years; 231 men) who underwent 435 CAS procedures at a large tertiary care center between January 1999 and December 2013. For analysis, patients were stratified based on their lesion type [de novo (dn) vs post-CEA restenosis (res)] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Among the clinical variables that were analyzed in this study, only younger age (< 70 years) was found to be statistically significant in the multivariate analysis. Mousa et al found that age < 65 years old was a significant predictor of restenosis [ 37 ]. With regard for peripheral arterial disease, young patients, who likely have a more aggressive form of systemic atherosclerotic disease, appear to be predisposed to requiring multiple procedures or reinterventions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the clinical variables that were analyzed in this study, only younger age (< 70 years) was found to be statistically significant in the multivariate analysis. Mousa et al found that age < 65 years old was a significant predictor of restenosis [ 37 ]. With regard for peripheral arterial disease, young patients, who likely have a more aggressive form of systemic atherosclerotic disease, appear to be predisposed to requiring multiple procedures or reinterventions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Similarly, there is no statistically significant difference in outcomes after CAS for treatment of de novo stenosis compared with CAS for restenosis after CEA. 27 As stents are being increasingly used for redo cases, expertise and experience in reoperative CEA may be decreasing, which may be partially responsible for the results observed in this study. 10,11 Improvements in surgical technique, patient monitoring, and perioperative therapy have progressively improved patient outcomes after primary CEA during the past two decades.…”
Section: Discussionmentioning
confidence: 92%
“…Many studies of restenosis included patients undergoing angioplasty alone and do not appear to reflect current ISR rates. A recent study found peripheral vascular disease to be an independent predictor of ISR 15. A long-term follow-up study by Baldi et al 16 evaluated patients treated with CAS up to 7 years after treatment and found ISR in 7.4%.…”
Section: Discussionmentioning
confidence: 99%